FRAME STRUCTURE OF THE CONCEPT " GOLD” IN NAVOI'S POEM " ISKANDER'S WALL” (Scientific journal of the Fergana State University, 2023)
This article examines the frame structure of the concept “gold” in Alisher Navoi's poem “Iskander's Wall”. First, a brief theoretical overview of the term concept and related concepts is given. Then we consider and substantiate the “gold” concept sphere used in the poem.